Evaluating the Field Practicum Experience in Social Work Fieldwork Programs Using an Online Survey Approach: Student and Supervisor Responses - Margaret Pack (Social Work and Society)
A key issue for busy education managers is how to design evaluative research to obtain quality and reliable data to enhance fieldwork programme development. This article provides a report of a small study conducted at one university in Australia which aims to explore the satisfaction of field supervisors and students with various aspects of the field education program. The author's main objective was to evaluate the operation of program to improve the day to day experience of the fieldwork program for students and their field supervisors. A secondary aim was to determine if students and field supervisors would engage and participate fully in an online survey approach to the evaluation, for the purposes of eliciting ideas and suggestions for improvement to be implemented by the program co-ordinators. METHOD: Using an online questionnaire built through the Qualtrix software, students and their fieldwork supervisors were asked individually about their experiences of the placement, communication with the University, preparation, and assessment. A low response rate was found, making generalisation across the student and fieldwork educators' cohorts problematic. FINDINGS: The results from participants suggest that the social work field supervisors need more support when supervising a student practicum, due to the changes occurring in their workplaces. Specifically, restructuring in the social services was reported as making it difficult to take on the additional responsibilities encompassed in the fieldwork supervision role. CONCLUSION: Whilst the feedback from students indicates are they generally pleased with the field supervisors' input, the field supervisors who responded state that they lack the time and resources to provide the requirements of student learning.